Effect of pranayama versus aerobic exercise on hematological parameters in women with iron-deficiency anemia - Youssef Mohamed, Shokry Mahmoud; Shehata Kelini, Kerolous Ishak; Mahmoud Ahmed, Shimaa Sayed; Elaziz Abd Elhady, Azza Abd; Fathy Ahmed, Karim Ahmed; Mohamed, Manal Mahmoud; Ali Ismail, Ali Mohamed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
A growing body of evidence shows that individuals with iron deficiency anemia have deficits in some of their hematological parameters that may be associated with increased fatigue, which affects their quality of life. This study aimed to differentiate between the efficacy of pranayama and aerobic exercise on hematological parameters in females with iron deficiency anemia. Sixty patients aged between 30 and 40 years were selected from the outpatient clinic of October 6 University Hospital and were randomly divided into two groups. Study group (I) (n=30) participated in 12 weeks of anemia medication, diet recommendations, and 50 minutes of yoga practice, divided into 15 minutes of asana, 30 minutes of pranayama, and 5 minutes of meditation, for six times/week. Control group (II) (n=30) participated in 12 weeks of medical treatment of anemia, dietary advice, and treadmill aerobic exercise sessions for six times per week. All subjects were assessed by a hematology analyzer, a six-minute walking test, and the fatigue severity scale before and after the treatment program. In both groups, there were statistically significant improvements in all assessed variables except lymphocytes (p<0.05), with a higher percentage of improvement in favor of group I. Pranayama is more effective than aerobic exercise in improving hematological parameters in females with iron deficiency anemia.